2018
DOI: 10.3390/jcm7120483
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Proteomics for the Early Diagnosis of Diabetic Nephropathy in Taiwanese Patients

Abstract: Diabetic nephropathy (DN) is a major complication in diabetic patients. Microalbuminuria testing is used to identify renal disease; however, its predictive value is questionable. We aimed to identify urinary biomarkers to early diagnosis nephropathy before identifiable alternations in kidney function or urine albumin excretion occurs. Proteomic approaches were used to identify potential urinary biomarkers and enzyme-linked immunosorbent assay was performed to verify the results. The data identified haptoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
(32 reference statements)
0
29
0
Order By: Relevance
“…Increased urinary AMBP levels have been associated with kidney damage 72 and tubular dysfunction in diabetic nephropathy 73 . In addition, several shotgun proteomic studies followed by verification via different assays (Western blot, MRM in small sample sizes (n ≤ 11), or ELISA), supported an upregulation of AMPB in patients of various CKD stages compared to healthy controls, in adipose tissue, urine as well as urine exosomes [74][75][76] . AMBP was also found to progressively increase in plasma of individuals with increasing CKD stage -from CKD1-2 to CKD3-4 and finally to CKD5-based on relative quantification by LC-MS/MS 77,78 or MRM 77 .…”
Section: Discussionmentioning
confidence: 95%
“…Increased urinary AMBP levels have been associated with kidney damage 72 and tubular dysfunction in diabetic nephropathy 73 . In addition, several shotgun proteomic studies followed by verification via different assays (Western blot, MRM in small sample sizes (n ≤ 11), or ELISA), supported an upregulation of AMPB in patients of various CKD stages compared to healthy controls, in adipose tissue, urine as well as urine exosomes [74][75][76] . AMBP was also found to progressively increase in plasma of individuals with increasing CKD stage -from CKD1-2 to CKD3-4 and finally to CKD5-based on relative quantification by LC-MS/MS 77,78 or MRM 77 .…”
Section: Discussionmentioning
confidence: 95%
“…The day before the renal CT angiography examination, fasting blood glucose (FBG), urinary albumin excretion rate, 24 h urinary protein quantitation (UPQ), blood urea nitrogen, serum creatinine, Cystatin C (Cys C) and random urine albumin to creatinine ratio (ACR) were measured on both of DN group and control group then the Scr value were conversed based on the new-old unit coefficient 0.01131 and further used to estimate eGFR by using equation: eGFR-MDRD=175×(Scr(mg/dl)) -1.234 × age -0.179 ×(female×0.79); the Cys C value were used to estimate eGFR based on the equations eGFR-cys=78.64×Cys C -0.964 [1,5,6].…”
Section: Detection Of Related Biochemical Indicesmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is one of the most common complication of type 2 diabetes mellitus (T2DM), it is estimated that approximately 20-40% of type 2 diabetes (T2D) patients will develop renal disease [1]. Early features include slight increase in urinary albumin excretion which may eventually develop into end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hp, through binding to monocytes, may also participates in anti-inflammatory process and immune regulation by preventing overproduction of TNF-α, IL-10, and IL-12 [10]. Clinical studies showed that urine Hp may be useful to predict T2DM patients at risk of nephropathy before the development of macroalbuminuria or reduced eGFR [11,12]. In acute kidney injury (AKI) mouse models, Hp levels in urine, plasma and renal cortical were all significantly increased and the proximal tubule was the dominant site of renal Hp expression.…”
Section: Introductionmentioning
confidence: 99%